The past perfect tense in Nigerian and British : a comparative corpus-based study - Ibrahim, Abidat Ademorin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
A comparison of a native variety of English with a non- native variety may help to identify and understand the latter's emerging and distinctive features. This study explored the frequency and lexico-grammatical patterns of the past perfect tense in British English (BrE) and Nigerian English (NigE). The past perfect tense constructions were obtained from the International Corpus of English (ICE) for data on BrE (ICE-GB) and NigE (ICE-Nig). The results revealed similarities in the frequency of the tense in most of the registers of ICE-GB and ICE-Nig. The two varieties were also similar in their choice of collocations of the tense since BrE and NigE where found to use largely similar verbs as the past participle of the past perfect tense. However, NigE appears to differ from the BrE in the choice of the accompanying time-marked adverbials. This study also reveals that the standard meaning of the past perfect tense had been extended in NigE. In particular, there were past perfect tense constructions which were found to express present perfect tense meaning. This extension in meaning can be explained by the influence of the tense and aspect system of the mother tongue (Yoruba, Igbo, and Hausa) which differs from that of English.